Effect of lemon water vapor extract (LWAE) from lemon byproducts on the physiological activity and quality of lemon fermented products. Issue 1 (1st January 2021) - Hsieh, Cheng-Yu; Ciou, Jhih-Ying; Shih, Ming-Kuei; Hsieh, Shu-Ling; Huang, Yu-Wen; Chen, Min-Hung; Hou, Chih-Yao
ABSTRACT: The byproducts of lemon juice have always constituted an environmental issue. In this study, the byproducts extracted to lemon water vapor extract (LWAE) by distilled, which was added to lemon fermented products (LFP) to evaluate its effect on its quality and bioactivity. Based on the gas chromatography-mass spectrometry results, the main component of the LWAE was D-limonene (>41%). After added 5% LWAE the amount of D-limonene in non-sterilized lemon fermented product (NLFP) increased from 10.1% to 20.9%, while that in LFP increase from 10.5% to 19.9%. Besides, anti-browning test results showed that LWAE could delay browning. This study demonstrated that LWAE improved the antioxidant capacity, limonene content, anti-browning ability, and bioactive ingredients in a gastrointestinal simulation. These results may serve as the principal basis for byproduct reuse and improvement of product quality.